Stock market reaction to covid-19: Evidence from Vietnam - Nguyen, Thi My Linh; Bui, Ngoc Toan (Journal of Finance - Marketing Research, 2022)
This paper examines the impact of the Coronavirus (Covid-19) epidemic on stock market returns. In particular, Covid-19 is determined through the number of confirmed cases and the number of deaths. The research data sample was collected in Vietnam, which is an emerging country with a nascent but rapidly developing stock market during the past time. For the analytical method, the Autoregressive Distributed Lag (ARDL) method is used to estimate the research model. The estimation results indicate that the stock market reacts negatively in both the short and long term to the information about the number of Covid-19 cases. In other words, stock market returns decline when the number of Covid-19 cases increases. However, the impact of Covid-19 deaths on stock market returns is negligible. This shows that the stock market usually reacts as soon as the number of Covid-19 cases is confirmed. Regarding Covid-19 deaths, it usually takes a certain time to update the number of Covid-19 deaths since the number of Covid-19 cases is confirmed. Moreover, Vietnam has treated Covid-19 cases quite well. Therefore, stock market investors often react insignificantly to the number of Covid-19 deaths. In addition, this study also finds the negative impact of inflation and interest rates on stock market returns. The results of this study are significant empirical evidence for Vietnam, especially in Covid-19 control and stock market development